2015
DOI: 10.1890/13-2113.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding protected area resilience: a multi‐scale, social‐ecological approach

Abstract: Abstract. Protected areas (PAs) remain central to the conservation of biodiversity. Classical PAs were conceived as areas that would be set aside to maintain a natural state with minimal human influence. However, global environmental change and growing cross-scale anthropogenic influences mean that PAs can no longer be thought of as ecological islands that function independently of the broader social-ecological system in which they are located. For PAs to be resilient (and to contribute to broader social-ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
168
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 104 publications
(122 reference statements)
4
168
0
19
Order By: Relevance
“…Following Walker et al (2006) and Cumming et al (2015), the cycles to be identified correspond to interactive processes ( Fig. 2) with growth phases regarding capital and resources (r), and followed by exploitation or maintenance of the system (K) generating reorganization processes (Ω) in which there is a possibility of saturation or collapse.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following Walker et al (2006) and Cumming et al (2015), the cycles to be identified correspond to interactive processes ( Fig. 2) with growth phases regarding capital and resources (r), and followed by exploitation or maintenance of the system (K) generating reorganization processes (Ω) in which there is a possibility of saturation or collapse.…”
Section: Methodsmentioning
confidence: 99%
“…This definition emphasizes that evolution of natural systems and social systems is interdependent. Studies focused on dynamics of SES (Berkes et al, 2003;Cumming and Collier, 2005;Janssen et al, 2007;Nyaupane and Poudel, 2011) differentiate adaptive cycles with phases of growth, maintenance, reorganization, innovation or collapse of the system -all of them emerging as responses to critical situations. This approach is based on a wide concept regarding changing phenomena related to function, structure and identity of complex systems.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The conservation community is moving towards more integrative and collaborative and approaches to conservation (Cumming et al, 2015;Guerrero et al, 2015;Tengö et al, 2017;Therville et al, 2017). As diverse teams are constituted to deliver real world solutions to pressing conservation problems, we hope that social scientists, artists and humanities scholars are amongst those represented.…”
mentioning
confidence: 99%